ChemInform Abstract: Studies on the Phthalidation of Heteroarenes: A Facile Preparation of 3‐(Heteroaryl)phthalides via Triflic Acid Mediated Phthalidation. Issue 33 (19th August 2014) - Nandakumar, Meganathan; Sankar, Elumalai; Mohanakrishnan, Arasambattu K.
Abstract This straightforward and general method provides access to mono‐, bis‐ and tris‐heteroarylphthalides through triflic acid‐mediated Friedel‐Crafts phthalidations.